2016
DOI: 10.32598/jccnc.2.4.201
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Quality of Life Among Female Sex Workers With and Without Addiction

Abstract: Background: Prostitution and substance abuse are among the crucial social problems in women, which affect the quality of life. However, no study has yet investigated that prostitution and substance abuse affect which dimension(s) of quality of life. The current study aimed to compare different dimensions of quality of life among female sex workers with and without drug abuse. Methods: The research design was ex post facto study. The study sample comprised 120 women (60 female sex workers with substance abuse a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
1
8
0
1
Order By: Relevance
“…Vulnerable women are not only deprived of emotional support, but also exposed to violence, humiliation, stigma and various physical, as well as mental and verbal discriminations in families and society [ 5 ]. Thus, they have been marginalized and stigmatized in the society [ 6 ]. Wechsberg et al concluded that addicted women were more vulnerable and could not protect themselves sexually [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vulnerable women are not only deprived of emotional support, but also exposed to violence, humiliation, stigma and various physical, as well as mental and verbal discriminations in families and society [ 5 ]. Thus, they have been marginalized and stigmatized in the society [ 6 ]. Wechsberg et al concluded that addicted women were more vulnerable and could not protect themselves sexually [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Depression is a pervasive disorder that affects many people at some point in their lives. Its prevalence is higher in poor than in rich people (Khodabakhshi-Koolaee et al, 2016B) and in women than in men (Young et al, 1990).…”
Section: Plain Language Summarymentioning
confidence: 97%
“…A review of various studies shows a high prevalence of high-risk sexual behaviors and the lack of awareness of sexually transmitted diseases among the temporary residents of homeless shelters in Tehran. It has been also shown that factors, such as illiteracy, the low awareness of high-risk behaviors, the high prevalence of these behaviors, being at reproductive age, and the lack of health-promoting behaviors threaten homeless women (Khodabakhshi-Koolaee et al, 2016A;Akhtarkhavari & Naderloo 2019;Khodabakhshi-Koolaee et al, 2016B).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, they have been marginalized and stigmatized in society [5]. Wechsberg et al concluded that addicted women were more vulnerable and could not protect themselves sexually [6].…”
Section: Introductionmentioning
confidence: 99%
“…Vulnerable women are deprived of emotional support, many of whom are exposed to violence, humiliation, stigma and various physical, mental and verbal discriminations in families and society [4]. Thus, they have been marginalized and stigmatized in society [5]. Wechsberg et al concluded that addicted women were more vulnerable and could not protect themselves sexually [6].…”
Section: Introductionmentioning
confidence: 99%